Wartime Shanghai and the Jewish Refugees from Central Europe Survival, Co-Existence, and Identity in a Multi-Ethnic City - Eber, Irene (De Gruyter, 2012)
The study discusses the history of the Jewish refugees within the Shanghai setting and its relationship to the two established Jewish communities, the Sephardi and Russian Jews. Attention is also focused on the cultural life of the refugees who used both German and Yiddish, and on their attempts to cope under Japanese occupation after the outbreak of the Pacific War.